Analisis Kompensasi dengan Pemanfaatan Plafon Rawat Jalan serta Rawat Inap terhadap Kepuasan Kerja Karyawan di PT XYZ Karawang - Nurdiansyah, Suhendar; Rumalutur, Ima Fudri; Nursyah, Muhammad; Karmansyah, Karmansyah; Munib, Munib; Mulyadi, Edi (Community Engagement and Emergence Journal (CEEJ), 2025)
The present investigation seeks to probe the impact of compensation, the utilization of outpatient service limits, also utilization of inpatient service limits on employee job satisfaction at PT XYZ Karawang, concurrently yet discretely. The genesis of this inquiry originates from differences in policies related to health service limits and plans for facility changes, which are expected to affect employee job satisfaction. This research executed a quantitative approach, structured via an associative investigational blueprint, with a sample totaling 78 respondents selected purposively from a total of 352 permanent employees. Data were amassed via structured questionnaires and subjected to analysis employing multiple linear regression, t-statistics, F-statistics, and the determinacy coefficient. The analytical elucidate that remuneration, the exploitation of outpatient service thresholds, and the engagement with inpatient service thresholds exert an affirmative and inferentially consequential influence upon personnel vocational contentment when assessed in isolation. When evaluated concurrently, these triad variables likewise manifest a substantial influence, accounting for 25.4% of the variance, whereas the residual 74.6% is attributable to exogenous factors beyond the purview of the present research model. These results indicate that fair compensation and adequate health facilities are crucial factors in fostering job satisfaction. The utilitarian import of this inquiry implies that management should maintain and enhance compensation policies as well as targeted health facilities to improve employee performance and loyalty.